Toward an Objective-Driven System of Smart Labor Migration Management - Holzmann, Robert; Pouget, Yann (World Bank, Washington, DC, 2012)
This policy note offers motivation and a game plan for achieving a coherent and mutually beneficial labor migration system. It argues that migrant workers may make important contributions to economic growth and development in both sending and receiving countries if they find enabling conditions. To achieve a potential win-win-win situation requires: (1) a sustainable migration management system that takes into account the interests of the various stakeholders involved; (2) a clear identification and articulation of objectives and interests in migration by key stakeholders, based on a common conceptual framework for migration and development; (3) regional and bilateral coordination mechanisms to balance these (potentially divergent) objectives and to reach compromise under labor agreements and policies; and (4) effective, evidence-based polices and public and private sector interventions to achieve the objectives that are known and applied at the levels of sending, receiving, returning, and circulating.